2021
DOI: 10.1093/cid/ciab417
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Evaluation of Probiotic Use for the Primary Prevention of Clostridioides difficile Infection

Abstract: Background Primary prevention of C. difficile infection (CDI) is a priority for hospitals and probiotics have the potential to interfere with colonization and infection with C. difficile. This study evaluated the impact of a computerized clinical decision support tool (CCDS) to prescribe probiotics for primary prevention of CDI among adult hospitalized patients. Methods A CCDS tool was implemented into the electronic medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Allen et al failed to show a statistically significant benefit of probiotics in the prevention of antibioticassociated diarrhea (AAD) or CDI [18]. A recent multi-center trial by Heil et al evaluated the impact of a computerized clinical decision support tool to prescribe probiotics to highrisk patients for primary prevention of CDI [19]. Over the 13-month post intervention period, 2489 patients (16.6%) received probiotics and no difference in CDI was observed compared to the pre-intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…Allen et al failed to show a statistically significant benefit of probiotics in the prevention of antibioticassociated diarrhea (AAD) or CDI [18]. A recent multi-center trial by Heil et al evaluated the impact of a computerized clinical decision support tool to prescribe probiotics to highrisk patients for primary prevention of CDI [19]. Over the 13-month post intervention period, 2489 patients (16.6%) received probiotics and no difference in CDI was observed compared to the pre-intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor—Two recent studies tested the same 3-strain Lactobacillaceae probiotic mixture for the prevention of Clostridium difficile infection (CDI), yet reported conflicting results [ 1 , 2 ]. In studies that test probiotics for CDI prevention, different efficacies are often reported, but typically it is due to not accounting for the strain-specific efficacy of probiotics [ 3 ].…”
mentioning
confidence: 99%
“…A review of 28 QES found that limitations included low implementation of the probiotic and not accounting for changes in infection control measures or antibiotic use during the 2 time periods [ 4 ]. With these limitations in mind, we examined these 2 studies to attempt to determine why the same probiotic was effective in the Maziade et al study [ 1 ] but not in the Heil et al study [ 2 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations